1989
DOI: 10.3109/08916938908997099
|View full text |Cite
|
Sign up to set email alerts
|

The Immunoglobulin Class, the Subclass and the Ratio of k:λ Light Chain of Autoantibodies to human Insulin in Insulin Autoimmune Syndrome

Abstract: The immunoglobulin class, subclass and the k:lambda light chain ratio of insulin autoantibodies were determined in the sera of twenty-four patients with insulin autoimmune syndrome. All sera proved to be of the IgG immunoglobulin class but exhibited various IgG1:IgG2:IgG3:IgG4 ratios. The ratio of k:lambda light chain ranged from 1:0.13 to 1:0.75 with the exceptions of two sera that were characterized as IgG1(k) and IgG1(lambda).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“… 27-31 They are most commonly of the IgG class without predominance of a particular subclass or light chain. 32 Further examination in this case confirmed the insulin-binding antibody to be IgG2 kappa, consistent with the paraprotein and increased serum concentration of IgG2. In the context of severe dysglycaemia requiring clinical intervention, discriminating the 2 entities had important management implications: although aberrant insulin kinetics are induced by a similar mechanism in both polyclonal IAS and monoclonal insulin binding, autoantibody production in IAS may be self-limiting, while in PCD, targeted PCDT is needed for antibody depletion.…”
Section: Discussionsupporting
confidence: 63%
“… 27-31 They are most commonly of the IgG class without predominance of a particular subclass or light chain. 32 Further examination in this case confirmed the insulin-binding antibody to be IgG2 kappa, consistent with the paraprotein and increased serum concentration of IgG2. In the context of severe dysglycaemia requiring clinical intervention, discriminating the 2 entities had important management implications: although aberrant insulin kinetics are induced by a similar mechanism in both polyclonal IAS and monoclonal insulin binding, autoantibody production in IAS may be self-limiting, while in PCD, targeted PCDT is needed for antibody depletion.…”
Section: Discussionsupporting
confidence: 63%
“…binding to human insulin (13) and the diversity of the ratio of K-to-\ light chain (26). HLA serological typing and DNA typing.…”
Section: Methodsmentioning
confidence: 99%
“…In the immunoprecipitation analysis using antibodies against human immunoglobulin heavy chains and light chains, only antibodies against human IgG and ĸ showed significantly increased precipitation of [ 125 I] human insulin compared to control, which indicated that immunoglobulin class of insulin autoantibodies was exclusively IgG-ĸ in the patient (table 1) [10]. These results strongly suggested that the patient had monoclonal insulin autoantibodies.…”
Section: Resultsmentioning
confidence: 57%
“…Immunoprecipitation analysis demonstrated that immunoglobulin class of insulin autoantibodies was exclusively IgG-ĸ. It has been described that a single binding affinity of insulin autoantibodies and ĸ or λ chain predominance in insulin autoantibodies are important features of monoclonal insulin autoantibodies [9, 10]. The present results, therefore, indicate that the patient has monoclonal insulin autoantibodies, which is extremely rare in Japan [4, 9].…”
Section: Discussionmentioning
confidence: 55%